What is the association between secondhand smoke (SHS) and possible obstructive sleep apnea: a meta-analysis - Chen-Wei Chang; Ching-Hsiung Chang; Hung-Yi Chuang; Han-Yun Cheng; Chia-I Lin; Hsiang-Tai Chen; Chen-Cheng Yang (BMC, 2022)
Highlights 1. This is a meta-analysis to evaluate the relationship between secondhand smoke (SHS) exposure and obstructive sleep apnea (OSA) in both adults and children. 2. Our meta-analysis revealed a significantly positive association between SHS exposure and possible OSA in children and adults. 3. Both smoking in mothers and fathers are associated with significantly higher risk of OSA in children.